Silver Nanoparticles Of Clinacanthus Nutans Aqueous Extract: Biosynthesis, Phytochemical And Selected Biological Activities - Che Mood, Che Nurul Azieyan (2018)
The use of plant to synthesise silver nanoparticles (AgNPs) is considered as a green technology. In this study, a non-toxic, cost effective and eco-friendly method has been applied to synthesise AgNPs using aqueous extract of leaf and stem of Clinacanthus nutans (C. nutans). The synthesised AgNPs were tested on antimicrobial, antioxidant and cytotoxicity activities. The formation of AgNPs was confirmed by UV-Vis spectroscopy at the wavelength of 420 nm (AgNP-L) and 430 nm (AgNP-S). The size were measured at 114 nm (AgNP-L) and 129 nm (AgNP-S) using a zetasizer. From TEM analysis, the size ranged from 10-300 nm and 10-180 nm for AgNP-L and AgNP-S with spherical shape. Zeta potentials recorded at -42.8 mV for AgNP-L and -43.9 mV for AgNP-S. XRD analysis matched the face-centered cubic (fcc) structure of silver. FTIR analysis revealed the presence of few functional groups of phenolic and flavonoid compounds which acts as the reducing agent in AgNPs synthesis. The AgNPs showed good inhibition against bacteria, but not fungus. Inhibition showed that highest against S. aureus with 11.35 mm (AgNP-L) and 11.52 mm (AgNP-S), while the lowest inhibition against E. coli with 9.22 mm (AgNP-L) and 9.25 mm (AgNP-S) in disc diffusion method. Same trend of result was reported for well diffusion method. In antioxidant assays, AgNP-L showed IC50 at 417.05 μg/mL and AgNP-S at 434.60 μg/mL (DPPH); 304.31 μg/mL (AgNP-L) and 326.83 μg/mL (AgNP-S) for ABTS, respectively.